Deep‐Blue Fluorescent Particles via Microwave Heating of Polyacrylonitrile Dispersions. Issue 6 (7th February 2017) - Go, Dennis; Jurásková, Alena; Hoffmann, Andreas; Kapiti, Gent; Kuehne, Alexander J. C.
Abstract : Deep‐blue fluorescent particles are obtained from polyacrylonitrile by microwave irradiation. A series of acrylonitrile and octadecylacrylate copolymer particles are produced via emulsion polymerization. Subsequent exposure to microwave irradiation induces a cyclization reaction, which is in the carbon fiber community known as stabilization but usually induced thermally. A π‐conjugated system is produced leasing to particles with blue fluorescence and quantum yields as high as 14%. Abstract : This study presents a new method to produce fluorescent particles. Established methods are based on the incorporation of conjugated dye molecules into dielectric polymer matrices or preparation of colloids, which are composed of fluorescent conjugated polymer. By contrast, this study presents a method where dielectric polyacrylonitrile is exposed to microwave radiation leading to an intramolecular cyclization reaction producing π‐conjugated segments, which fluoresce blue. During this conversion, the particles shrink in diameter but as an ensemble they retain their monodispersity. This work investigates the optimal reaction conditions and characterizes the optical properties.